Estudo do comportamento tribológico do politetrafluoretileno em deslizamento sem lubrificação contra aço inoxidável - Vale, Jõao Luiz do (2014)
This work discusses the tribological behavior of polytetrafluoroethylene (PTFE), a polymer widely used in industry for many tribological applications without lubrication, from where you can highlight its use as plain bearings. A literature review was done to understand the main parameters that influence kinetic friction and wear of polymers and the wear mechanisms that operate in these materials. Long tests duration were conducted on a machine of kinetic friction, developed and built at the Laboratory for Surface and Contact (LASC) UTFPR, in which a polymer bushing slides without lubrication on a metal shaft. This condition simulates a real application of PTFE as bearing. These experimental procedures are fundamental to the complete analysis of the characteristics and performance of polymeric materials in tribological applications, which usually show a complex behavior. In the tests was observed that the parameters of kinetic friction coefficient and temperature stabilized after 80 minutes. The first parameter decreased with the normal load and the temperature, in its turn, kept proportional with the product of kinetic coefficient of friction and the square root of the applied normal force. Analyses were performed on the surfaces, before and after tests, using techniques of white light interferometry, scanning electron microscopy, FTIR and DSC. It was found that the wear mechanisms which operated were: adhesive and abrasive, and the first one was dominant. The stainless steel surfaces had subtle changes, while the PTFE surfaces had drastic changes. The values for the PTFE mass wear rate were proportional to the square root of the applied normal force and the dimensionless coefficient of wear for the system had satisfactory approximation to the values available in the literature. It was found that the wear particles merged in multilayer films. These multilayer films were expelled from contact with the test sequence and exhibit translucent appearance, increasing the degree of crystallinity than the material and changes in the infrared spectra. These changes suggest the substitutions occurrence of fluorine for hydrogen in the structure of PTFE during tests.